Privacy the work for public benefit punishment - العامري, سامر سعدون; جالي, فريال صالح (Journal of Legal Sciences, 2021)
Work for public benefit (Community service) is a criminal punishment that restricts liberty. The convicted person performs an unpaid work for public benefit, The judge determine in the ruling the number of working hours and the period of completion within the limits set by the law. It is a new and unique punishment that involves punitive treatment outside the prison walls. It spawned of the necessities of rehabilitative justice to Confrontation the crisis of the punishment for deprivation of liberty for a short period (custody). The main aim of the work penalty for public benefit is to rehabilitate the convict to reintegrate him socially, which is the first rank among the aims of punishment under contemporary punitive policy. This punishment has been very successful in the criminal justice field, It includes rehabilitation, social and economic advantages that made it occupy the forefront in the list of punitive alternatives.